The association between Vitamin D and clinical IVF outcomes, and the in vitro effects of Vitamin D on granulosa cell steroidogenesis and metabolism - Walz, Nikita Lee (Curtin University, 2021)
In recent years, studies have investigated the clinical importance of VitD levels in human fertility, but little is known about how VitD impacts women undergoing IVF or reproductive cells at the molecular level. This study has demonstrated that VitD significantly impacts the development of blastocysts and key molecular pathways involved in steroidogenesis and cellular metabolism. In the future these findings could help us improve clinical procedures in IVF to optimise patient clinical outcomes.